Challenges of using critical swimming velocity. From Scientists to coaches - Dekerle, J.; Pelayo, P.; Sidney, M.; Brickley, G. (Biomechanics and Medicine in Swimming X, 2006)
So far, a few studies have been conducted on the Critical swimming velocity concept. The current available knowledge suggests there is merit in using CV for training. The model offers Potential to swimming in that it is non-invasive and easy to administer. The CV concept appears as a useful tool for setting training intensities, monitoring training effects, and predicting performances. All these applications are reviewed in the present article.